Konvergensi Radio Attaqwa Bekasi dalam Mempertahankan Eksistensinya di Era Digital - Pramudita, Hesti; Ramdhani, Muhamad; Ema, Ema (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
The advancement of information and communication technology has encouraged mass media to transform into the digital era. This change has forced conventional media to adapt to technological developments to remain relevant in the digital era. This study aims to describe the implementation of media convergence at Radio Attaqwa Bekasi in maintaining its existence in the digital era. The focus of the study covers three aspects of media convergence according to Henry Jenkins, namely multimedia, multichannel, and multiplatform. The method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and documentation of Radio Attaqwa Bekasi managers. The results show that Radio Attaqwa Bekasi has implemented a convergence strategy in the form of broadcasting via YouTube live streaming (multimedia), broadcast distribution through websites and social media (multichannel), and broadcasts that can be accessed through the Radio Online Indonesia application on smartphones (multiplatform). The implementation of media convergence carried out by Radio Attaqwa Bekasi has resulted in several successes in increasing audience reach, two-way interaction with the audience, and expanding the demographic diversity of listeners. However, in the implementation process, Radio Attaqwa Bekasi also faces several challenges such as limited funds, limited human resources, and consistency in content production. This study concludes that the implementation of media convergence on Attaqwa Bekasi Radio broadcasts has been running so that it can increase the existence and relevance of the da'wah-based radio community amidst changes in people's media consumption behavior, but there is still a need for improvement in the consistency of content conservation and optimization of the use of digital platforms so that broadcasts can be maximized.